The Anxiety Levels and Mathematical Literacy of the Eighth Grade Indonesian Students on Quantity Content - Asyari, Syahrullah; Nasrullah; Barakat Hussein, Hisham; Nuraeni (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Mathematical literacy is essential for students’ academic success and real-life problem-solving. However, math anxiety remains a significant barrier affecting students' performance, particularly in the “quantity” content of mathematical literacy. Despite extensive research, limited studies have explored how varying levels of math anxiety influence students’ mathematical literacy in specific content domains. This qualitative descriptive study investigates the impact of math anxiety on the mathematical literacy of the eighth-grade students in the “quantity” content. Using purposive sampling, six students from State Junior High School 26 Makassar were selected. The data collection involved a math anxiety questionnaire, a mathematical literacy test, and interview guidelines. The Miles, Huberman, and Saldana model was applied for data analysis. The findings indicate that math anxiety levels strongly influence students’ mathematical literacy. Students with low anxiety demonstrated strong conceptual understanding, effective problem-solving strategies, and accurate calculations. Those with moderate anxiety managed simpler tasks but struggled with complex problems, consistent with the Yerkes-Dodson law. The students experiencing high anxiety exhibited the poorest performance faced challenges in understanding instructions and applying appropriate strategies. The study highlights the necessity of addressing math anxiety through interactive teaching approaches and targeted support to enhance students’ mathematical literacy, suggesting practical interventions for educators. Abstrak: Literasi matematika sangat penting untuk keberhasilan akademik siswa dan pemecahan masalah dalam kehidupan nyata. Namun, kecemasan matematika tetap menjadi hambatan signifikan yang memengaruhi kinerja siswa, terutama dalam konten “kuantitas” literasi matematika. Meskipun penelitian yang luas telah dilakukan, hanya sedikit studi yang mengeksplorasi bagaimana tingkat kecemasan matematika yang berbeda memengaruhi literasi matematika siswa dalam domain konten tertentu. Studi deskriptif kualitatif ini menyelidiki dampak kecemasan matematika terhadap literasi matematika siswa kelas delapan dalam konten “kuantitas”. Melalui teknik purposive sampling, enam siswa dari SMP Negeri 26 Makassar dipilih sebagai responden. Pengumpulan data melibatkan kuesioner kecemasan matematika, tes literasi matematika, dan pedoman wawancara. Model Miles, Huberman, dan Saldana digunakan untuk analisis data. Hasil penelitian menunjukkan bahwa tingkat kecemasan matematika sangat memengaruhi literasi matematika siswa. Siswa dengan tingkat kecemasan rendah menunjukkan pemahaman konsep yang kuat, strategi pemecahan masalah yang efektif, dan perhitungan yang akurat. Siswa dengan tingkat kecemasan sedang mampu menangani tugas-tugas sederhana tetapi kesulitan dengan masalah yang lebih kompleks, sesuai dengan hukum Yerkes-Dodson. Siswa dengan tingkat kecemasan tinggi menunjukkan kinerja terburuk, menghadapi kesulitan dalam memahami instruksi dan menerapkan strategi yang sesuai. Studi ini menyoroti pentingnya mengatasi kecemasan matematika melalui pendekatan pengajaran interaktif dan dukungan yang ditargetkan untuk meningkatkan literasi matematika siswa, serta merekomendasikan intervensi praktis bagi para pendidik.